Pengaruh Bentuk Sediaan Jahe Emprit (Zingiber officiale Var. Amarum) Terhadap Cemaran Logam Berat Tembaga (Cu) dan Timbal (Pb) Menggunakan Metode Spektrofotometri Serapan Atom - Susanti, Mita; Candra, Searly Riska; Ampur, Angela Desiani (LPPM Sekolah Tinggi Ilmu Farmasi Nusaputera, 2024)
Indonesia ranks 5th in the world with production of 183.5 tons of ginger in 2020. Emprit ginger (Zingiber Officinale Var Amarum) contains essential oils, oleosin and starch. The high content of essential oils in emprit ginger is 1.5% - 3.5%, so emprit ginger has the potential to be used as a traditional medicine. When processing ginger into traditional medicine, it can be made in different dosage forms such as powder and extract. Heavy metal contamination is a quality requirement that needs to be considered in the manufacture of traditional medicine, one of the metals that contaminates rhizomes is copper (Cu) and lead (Pb). The aim of this research is to determine the effect of the dosage form of emprit ginger (Zingiber Officiale Var. Amarum) on heavy metal contamination of copper (Cu) and Lead (Pb) using the Atomic Absorption Spectrophotometry method. The type of research used was experimental research, with the independent variable being the dosage form of emprit ginger, namely powder and thick extract and the dependent variable being the levels of the heavy metals Cu and Pb. The method used in the analysis used the Atomic Absorption Spectrophotometry method and was carried out 3 times. The results of the levels of heavy metals Cu and Pb were then analyzed using the T-test to determine the effect of dosage form on contamination of heavy metals Cu and Pb. The results showed that the dosage form had no effect on the levels of heavy metals Cu and Pb with a value of (p>0.05).